Theoretical study on the optical properties of a phase change material blind in a double skin facade system - Li, Yilin; Peng, Yuke; Jing, Huaiwang; Fu, Sipeng (Frontiers in Built Environment, 2023)
The use of a phase change material (PCM) blind system has great potential in mitigating overheating issues in double skin facade (DSF) systems while maintaining their optical and thermal benefits. However, there is a lack of research information available regarding the optical properties of such systems. This paper establishes a solar radiation model of PCM blinds for use in a DSF system that integrates the optical path of sunlight. The influences of the solar incidence angle, slat inclination angle, the ratio of slat distance to slat width, and slat surface material on the optical coefficient of the blind system are analyzed. The results indicate slat inclination angle significantly affects diffuse absorptance and diffuse transmittance, while solar incidence angle has little impact. Diffuse absorptance gradually increases with increasing slat inclination angle, reaching a peak at 90°, while diffuse transmittance decreases. The optical coefficient of the blind is closely related to the ratio of slat distance to slat width. The smaller the slat inclination angle, the more noticeable the difference in absorptance or transmittance of direct/diffuse solar radiation. The reflectance of the blind surface material has a significant effect on the optical coefficient. As the reflectance of the slat surface material increases, both direct absorptance and diffuse absorptance of the slat show a decreasing trend. Our results suggest that this method could be used for optical properties measurement in PCM blind system. The results of this study provide effective references for the final selection of PCM and the estimation of component dosage.